Mapping the Structure of Tourist Space in the North Bandung Conservation Area - Pratama, Armandha Redo; Hindayani, Purna; Rosita, Rosita; Sukriah, Erry (Journal of Indonesian Tourism, Hospitality and Recreation, 2023)
ABSTRACTSustainable land management is a concept that is integrated between various aspects. This research uses a quantitative approach with the aim of mapping the tourism spatial structure in the North Bantung Conservation Area (KBU). It is recorded in West Java Provincial Government data (2021) that 20.4% of (TAOs) in West Java is in the North Bandung area. So this has great potential in terms of the number of tourist visits. Apart from that, the geographical position of the North Bandung area which is close to other metropolitan cities means that (TAOs) in this area increasingly has large tourist market potential. As a result, the development of tourism and its supporting facilities will also accelerate. This condition will certainly encourage land conversion activities. The occurrence of land conversion in KBU requires control in the implementation stage of space use patterns. The results of the analysis show that creating appropriate zoning in the tourist space structure is an important step in maintaining the authenticity of nature and culture in the North Bandung area. The use of tourist areas in this zone places more emphasis on the ecotourism aspect, with development potential covering an area of 16331.20 hectares located in zone I A (prohibited zone). The next development direction is level I and II buffer zones. The buffer zone is a zone that can be used for the construction of secondary or conditional facilities.ABSTRAKPengelolaan lahan berkelanjutan merupakan sebuah konsep yang terintegrasi antara berbagai aspek. Penelitian ini menggunakan pendekatan kuantitatif dengan tujuan untuk memetakan struktur ruang wisata di Kawasan Konservasi Bantung Utara (KBU). Tercatat dalam data Pemerintah Provinsi Jawa Barat (2021) sebesar sebesar 20,4% ODTW di Jawa Barat terdapat di Kawasan Bandung Utara. Sehingga hal tersebut menjadi potensi yang besar dalam hal jumlah kunjungan wisatawan. Disamping itu posisi geografis Kawasan Bandung Utara yang memiliki jarak yang dekat dengan kota metropolitan lainnya menjadikan ODTW di kawasan ini semakin memiliki potensi pasar wisatawan yang besar. Hasilnya perkembangan pariwisata dan fasilitas pendukungnya juga akan semakin pesat. Kondisi ini tentu akan mendorong kegiatan alih fungsi lahan. Terjadinya   alih   fungsi   lahan   di   KBU   memerlukan   pengendalian   dalam   tahap pelaksanaan pola pemanfaatan ruang. Hasil analisis menunjukkan bahwa pembuatan zonasi yang tepat dalam struktur ruang wisata merupakan langkah penting dalam menjaga keaslian alam dan budaya di kawasan Bandung Utara. Pemanfaatan kawasan wisata di zona ini lebih menekankan kepada aspek ekowisata, dengan potensi pengembangan seluas 16331,20 Ha yang berada pada zona I A (zona terlarang). Arahan pengembangan selanjutnya ialah zona penyangga tingkat I dan II. Zona penyangga merupakan zona yang dapat dimanfaatkan untuk pembangunan fasilitas sekunder ataupun kondisional.